PENGARUH PENGENDALIAN INTERNAL DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi pada Bendahara SKPD Se-Kabupaten Buol) - Nuraini, Nuraini; Muslimin, Muslimin; Kahar, Abdul (Katalogis, 2018)
The study aims to describe: 1) simultaneous influence of internal control and adherence to accounting rules on the tendency of accounting fraud on treasurers in governmental working units in Buol District; 2) significant influence of internal control, partially on the tendency of accounting fraud on treasurers in governmental working units in Buol District; 3). significant influence of adherence to accounting rules on the tendency of accounting fraud, partially on treasurers in governmental working units in Buol District. Statistical results using multiple linear regressions analysis with SPSS 16.0 finda that : 1) internal control and adherence to accounting rules have simultaneous influence on the tendency of accounting fraud on treasurers in governmental working units in Buol District; 2) internal control partially has positive and significant influence on the tendency of accounting fraud on treasurers in governmental working units in Buol District; 3) adherence to accounting rules partially has positive and significant influence on the tendency of accounting fraud on treasurers in governmental working units in Buol District.